Studi perbedaan antara model pembelajaran think talk write dan example non example terhadap keterampilan menulis narasi ditinjau dari motivasi belajar pada peserta didik kelas iv sekolah dasar - Slamet Slamet; Siti Istiyati; Annisa' Nur Latifah (Didaktika Dwija Indria, 2019)
The goals of this research to find out: (1) the different of narrative writing skills between students that teached using Think Talk Write learning model with Example Non Example learning model; (2) differences in narrative writing skills between students who hashigh learning motivation and low learning motivation; (3) the interaction between learning models and learning motivation trough narrative writing skills. This research is quantitative experimental with 2x2 factorial design. The technique to got sample using cluster random sampling. Two WaysAnava was used to analys the data with a significance level of 0.05.The results of thisresearch were (1) there was a different in narrative writing skills between students who teached by Think Talk Write learning model with Example Non Example learning model with FA = 6.259; (2) there was a different in narrative writing skills between the high learning motivation and low learning motivation with FB = 35,688; (3) there is no interaction between the learning model and learning motivation towards narrative writing skills as indicated by FAB = 0.628.             Keyword: think talk write, example non example, narrative writing skills, elementary school